2018
DOI: 10.1042/etls20170157
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous and dynamic marine shelf oxygenation and coupled early animal evolution

Abstract: It is generally agreed that early diversification of animals and significant rise of atmospheric and oceanic oxygen (O2) levels occurred in the Ediacaran (635–541 million years ago, Ma) and early Cambrian (ca. 541–509 Ma). The strength and nature of their relationship, however, remain unclear and debated. A recent wave of paleoredox research — with a particular focus on the fossiliferous sections in South China — demonstrates high spatial heterogeneity of oceanic O2 (redox) conditions and dynamic marine shelf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(31 citation statements)
references
References 77 publications
0
30
0
1
Order By: Relevance
“…There are multiple lines of evidence in support of water‐column oxygenation of marine shelves/basins during the early Cambrian, particularly on the Yangtze Block of South China (e.g., Fe speciation and RSTEs: Cheng et al, , Jin et al, ; Li et al, ; and Mo‐U isotope: Chen et al, , Cheng et al, ; Dahl et al, ), although the deep ocean is likely to have remained anoxic at that time (Sperling et al, ; Stolper & Keller, ). Early Cambrian surface‐ocean oxygenation is likely to have been driven by rising atmospheric O 2 levels (Li et al, , ). Long‐term expansion of the oxygenated ocean‐surface layer would have caused a downward movement of the O 2 /H 2 S redoxcline and progressive water‐column oxygenation, as recorded by intermediate‐depth sections such as Silikou.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple lines of evidence in support of water‐column oxygenation of marine shelves/basins during the early Cambrian, particularly on the Yangtze Block of South China (e.g., Fe speciation and RSTEs: Cheng et al, , Jin et al, ; Li et al, ; and Mo‐U isotope: Chen et al, , Cheng et al, ; Dahl et al, ), although the deep ocean is likely to have remained anoxic at that time (Sperling et al, ; Stolper & Keller, ). Early Cambrian surface‐ocean oxygenation is likely to have been driven by rising atmospheric O 2 levels (Li et al, , ). Long‐term expansion of the oxygenated ocean‐surface layer would have caused a downward movement of the O 2 /H 2 S redoxcline and progressive water‐column oxygenation, as recorded by intermediate‐depth sections such as Silikou.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding carbon and sulfur isotope data from carbonates, it is now recognized that (a) local oceanographic and diagenetic controls play a major role on the resulting signals and (b) isotopic data cannot be simply read in a mass‐balance framework relating burial of oxidized and reduced species (Ahm et al, ; Fike, Bradley, & Rose, ; Miyazaki et al, ). The Avalon Peninsula succession may have become more oxygenated in the mid‐Ediacaran, but new iron speciation data from other successions, as well as recent reports of banded iron formations in the Cambrian (Li, Cheng, et al, ; Li, Zhang, et al, ), demonstrate this was likely a regional phenomenon and that widespread deep‐water anoxia persisted into the Paleozoic (Sperling et al, ). Consistent with this picture, new uranium isotope data from carbonates demonstrate extensive (if sporadic) anoxia in the late Ediacaran and early Cambrian (Tostevin et al, ; Wei et al, ; Zhang et al, )—the ocean clearly did not become fully oxygenated after the Gaskiers glaciation.…”
Section: Point–counterpoint Argumentsmentioning
confidence: 99%
“…For example, the “Canfield ocean” featured anoxic and euxinic (sulfide‐rich) deep‐ocean conditions through the Proterozoic, relieved only by a relatively unidirectional rise in oxygen during the late Ediacaran (Canfield, ). Broader stratigraphic and geographic coverage, including onshore–offshore transects, as well as new redox proxies have provided a more nuanced view of Proterozoic redox with much less stability (Diamond & Lyons, ; Doyle, Poulton, Newton, Podkovyrov, & Bekker, ; He et al, ; Li, Cheng, et al, ; Li, Zhang, et al, ; Planavsky, Cole, et al, ; Planavsky, Slack, et al, ; Sperling et al, ; Tang, Shi, Wang, & Jiang, ). Any attempts to model Proterozoic redox conditions are similarly left with the conclusion that the marine redox landscape was patchy and complicated (Reinhard, Planavsky, Olson, Lyons, & Erwin, ).…”
Section: Myths About Oxygen and The Rise Of Animalsmentioning
confidence: 99%
“…Although more data are needed from various continental margins for a global chemostratigraphic correlation, gradually decreasing εNd(t) values of shallow-marine carbonates as well as phosphatic rocks in this study support a gradually more extensive and intensive continental orogeny during the assembly of Gondwana from the middle Ediacaran to early Cambrian (Li et al, 2008Zhao et al, 2018). Tectonic and magmatic processes are proposed closely linked with Precambrian atmospheric oxygenation (Campbell and Allen, 2008;Planavsky, 2018;Li et al, 2018). The net accumulation of atmospheric O2 is generally determined by the fluxes of O2 production and consumption.…”
Section: Potential Links Between Increased Continental Denudation Andmentioning
confidence: 53%
“…More effective oxygenic photosynthesis by eukaryotic algae was commonly considered to have produced more oxygen in the late Neoproterozoic (e.g., Brocks et al, 2017) while the net accumulation of oxygen is also determined by the changing consumption of oxygen by reductants. Tectonic controls on Earth-surface oxygenation have also been invoked in previous research (e.g., Kump and Barley, 2007;Campbell and Allen, 2008;Lee et al, 2016;Planavsky, 2018;Li et al, 2018) although tectonic drivers have not been comprehensively demonstrated by geochemical records. In particular, variations in continental denudation as well as global oceanic circulation following Gondwana amalgamation from the middle Ediacaran to early Cambrian are not well constrained.…”
Section: Introductionmentioning
confidence: 99%